2001
DOI: 10.1164/ajrccm.164.2.2006154
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Monocyte Chemoattractant Protein-1 and Pulmonary Vascular Resistance in Chronic Thromboembolic Pulmonary Hypertension

Abstract: The pathogenesis of severe pulmonary hypertension seems to be related to inflammatory response in diseased sites. Monocyte chemoattractant protein-1 (MCP-1) has been reported to play a role in the development of congestive heart failure. In this immunological response, activation and migration of leukocytes including macrophages to the inflammatory region are important factors. We hypothesized that the severity of pulmonary hypertension may be related to MCP-1, which is thought to be upregulated by blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
86
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 26 publications
9
86
5
2
Order By: Relevance
“…11) Circulating monocyte chemoattractant protein-1 has been found to correlate with PVR in CTEPH patients. 22) Our findings confirm and contribute previous studies, in which used different inflammatory biomarkers, on the usefulness of NLR to correlate preoperative PVR and also to predict mortality. 9,23) In addition, NLR was positively correlated with PVR, supporting the hypothesis that inflammation is an important process on PVR in patients with CTEPH.…”
Section: Discussionsupporting
confidence: 90%
“…11) Circulating monocyte chemoattractant protein-1 has been found to correlate with PVR in CTEPH patients. 22) Our findings confirm and contribute previous studies, in which used different inflammatory biomarkers, on the usefulness of NLR to correlate preoperative PVR and also to predict mortality. 9,23) In addition, NLR was positively correlated with PVR, supporting the hypothesis that inflammation is an important process on PVR in patients with CTEPH.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study showed that monocyte chemoattractant protein-1 is produced in endothelial cells, mononuclear cells, and smooth muscle cells in the fibrinous portion adjacent to the vascular lumen in endarterectomized tissue. 18 Herve and Fadel speculated that macrophages infiltrating the wall of an occluded pulmonary artery stimulate proliferation of the vasa vasorum and lead to delivery of bone marrow-derived endothelial progenitor cells for local vasculogenesis within the nonresolving clots. 6 Other nonhemodynamic factors that are elevated in patients with CTEPH, such as endothelin-1, 19 might play a role in development of dilated BAs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, while each may have a different pathobiology and natural history, histopathologic studies suggest a number of similarities in the vascular changes in CTEPH and CHD-PAH to those seen in idiopathic PAH [29,30]. As in PAH, recent work also suggests a role for inflammation in the genesis of CTEPH [31].…”
Section: Discussionmentioning
confidence: 99%